2009
DOI: 10.1038/oby.2009.153
|View full text |Cite
|
Sign up to set email alerts
|

Toward Objective Monitoring of Ingestive Behavior in Free‐living Population

Abstract: IntroductIonRates of overweight and obesity are increasing globally. The World Health Organization estimated that there were ~1.6 billion overweight and at least 400 million obese adults worldwide in 2005 and that there will be 2.3 billion overweight and 700 million obese adults worldwide by 2015 (ref. 1). Overweight and obese individuals have an increased risk of developing chronic diseases such as type 2 diabetes, cardiovascular disease, and cancer (2-5).Overweight and obesity result from an imbalance betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
68
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 65 publications
(70 citation statements)
references
References 22 publications
2
68
0
Order By: Relevance
“…These results are concordant with conclusions derived from a chewing and swallowing sensor, which found that there appeared to be no correlation between mass per chew/swallow and BMI [1]. Although to our knowledge, experiments comparing time length of meals and BMI have not been conducted, several studies manipulated eating rates using universal eating monitors and compared meal duration in obese and lean participants [17,18].…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…These results are concordant with conclusions derived from a chewing and swallowing sensor, which found that there appeared to be no correlation between mass per chew/swallow and BMI [1]. Although to our knowledge, experiments comparing time length of meals and BMI have not been conducted, several studies manipulated eating rates using universal eating monitors and compared meal duration in obese and lean participants [17,18].…”
Section: Discussionsupporting
confidence: 72%
“…Feedback data on body weight and total daily intake has been used to successfully modify weight behavior [1]. However, these apps do not including timing and speed of eating behavior.…”
Section: Introductionmentioning
confidence: 99%
“…Estimation of the mass ingested could be achieved through the counts of chews [13] and the type and caloric density of food could potentially be determined by adding a camera triggered by the detection algorithm [19]. Ingested mass could also be predicted by acoustic recognition of chewing cycles and food types.…”
Section: Discussionmentioning
confidence: 99%
“…The size selected for the epoch was found to present the best tradeoff between the frequency of physiological events such as bites, chewing and swallowing and time resolution of FI monitoring [11], [13]. The mean absolute value (MAV) of the signal SF 1 ( t ) within e i was computed as M AVei=1Ntruek=1Nfalse|xkfalse|where x k is the k th sample in an epoch e i of SF 1 ( t ) containing a total of N samples.…”
Section: Sensor Fusion and Pattern Recognition Methodologymentioning
confidence: 99%
See 1 more Smart Citation